(untitled) (Research, Society and Development, 2020)
Cancer has been characterized as a major public health problem due to its high prevalence in both developed and developing countries. In this sense, the practice of physical activity and food is one of the alternatives in the prophylaxis of cancer. This article aims to demonstrate the importance of physical activity as well as healthy eating in cancer prophylaxis. This is an integrative literature review conducted through the databases of the Virtual Health Library (VHL), Scientific Electronic Library Online (SCIELO) and Latin American and Caribbean Literature in Health Sciences (LILACS) and Medical Literature Analysis and Retrieval System Online) MEDLINE. 35 articles were selected where only seven were part of the final sample. In view of the results obtained, it became evident that the practice of physical activity is essential in the prophylaxis of cancer, as well as the adoption of a healthy diet, the results are very positive in the treatment of breast cancer, as well as in children and the population elderly. This consequently improves the patients’ physical and mental conditioning, as well as a better quality of life, increasing the chances of a cure for the disease. Therefore, the present research is limited to the benefits of physical activity and healthy eating in the prophylaxis of cancer. Given the above, the importance of studies like these is evident, since they contribute directly to scholars in the field, as well as to literature.